Agenda and Public Policy: Evidence from Chile - Olavarria-Gambi, M (Taylor and Francis Inc., 2016)
Based on Kingdon’s model and the punctuated equilibrium theory, this article analyzes the process of four Chilean public policies from 1990 to 2013. Evidence was collected from 205 interviews, official documents, 3,905 press clippings, and academic literature. Grounded theory was employed to analyze interviews. The analysis shows a tacit alliance between power and expert knowledge, that presidential motivation seems to be a key factor for an idea to be included in government agenda, that Chile’s policy-making process is rather elitist, and that its characteristics coincide with the “inside access model of agenda building.” © 2016 Taylor & Francis.